Essential PowerShell for Office 365 Managing and Automating Skills for Improved Productivity - Catrinescu, Vlad (Apress, 2018)
Take your Office 365 skills to the next level. Master PowerShell for Office 365 to stay competitive in today's world of highly sought after cloud management skills. With expert guidance, IT pros will learn how to leverage the muscle of PowerShell to automate many advanced administrative tasks not otherwise accessible in the Office 365 Admin Center. You will discover how to unlock configuration options and automate tasks in order to free up valuable time and resources. This book is your companion to administering Office 365 with PowerShell. You will learn time-saving techniques such as how to streamline administrative tasks, and how to manage users, licenses, and Office 365 services. Expert and MVP Vlad Catrinescu introduces each chapter with an overview and basic fundamentals, such as how to connect to your required service in Office 365, so that you have a solid foundation for success. Benefit from learning the theory behind PowerShell for Office 365 and put your knowledge to practice with numerous hands-on code examples. What You'll Learn: Manage users in bulk Export data such as user lists and groups Create and manage Office 365 groups Manage Exchange online distribution lists, mailboxes, and contacts Configure Skype for Business settings Perform compliance searches directly from PowerShell This book is for any IT pro who needs to manage Office 365 or one of its services such as Exchange, SharePoint, or Skype for Business. Readers should have a basic knowledge of PowerShell and the Office 365 service they want to manage. Vlad Catrinescu is a SharePoint and Office 365 consultant specializing in PowerShell, SharePoint, and hybrid scenarios. As an MVP, Microsoft Certified Trainer, and recognized international speaker, Vlad has helped hundreds of thousands of IT pros across the globe to get the most out of their SharePoint and Office 365 deployments. Vlad writes the popular "Absolute SharePoint Blog" and is a recipient of the "Top 25 Office 365 Influencers" award. His contributions can be found on sites such as CMSWire and ComputerWorld. He is the author of Deploying SharePoint 2016 (Apress).